MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MELALUI PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) DALAM PEMBELAJARAN IPS KELAS V SEKOLAH DASAR - Triningsih; Wardatussa’idah, Indah; M. Kurnianti, Endang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the problem-solving skills of fifth-grade students in social studies learning through the application of the Project Based Learning (PjBL) model. This study uses the Classroom Action Research (CAR) method by Kemmis and McTaggart, carried out in two cycles. Each cycle includes the stages of planning, action and observation, as well as reflection. The subjects of the study were 29 fifth-grade students of SDN Karet 01 Pagi Jakarta in the 2025/2026 academic year. Data collection techniques included tests, observations, and documentation. The instruments used consisted of problem-solving ability test questions and observation sheets of teacher and student activities. The data were analyzed descriptively, both quantitatively and qualitatively, based on the results of tests, observations, and field notes. The results of the study indicate that the application of the PjBL model can improve students' problem-solving skills. At the end of cycle II, as many as 82.7% of students obtained a score ≥70, thus surpassing the established success criteria, which was 75% of students achieving a score ≥70. In addition, teacher and student activities during learning reached 84.3% and 82.8% respectively, with a good category. These results indicate that the application of the PjBL model can improve students' problem-solving abilities in social studies learning for fifth-grade students at SDN Karet 01 Pagi Jakarta.